The Moment of Surprise and Dialogical Play. A Hermeneutical Inquiry into the Interhuman - David-Augustin Mândruț (Phainomena)
The contribution investigates the relationship between dialogue, time, and surprise. My proposal is that, in the case of dialogical face-to-face encounters, one ought to speak about a creative temporality. Such creative temporality is achieved by virtue of the moment of surprise, as it was thematized in the works of Martin Buber and Hans-Georg Gadamer. Although the two authors did not concern themselves necessarily with the issue of the temporality of dialogue, Henri Bergson’s scattered remarks on time and creativity might provide sufficient ground to delve into the question of the temporality of dialogue. In the present paper, I start with Claude Romano’s contemporary framework of “evential hermeneutics,” in which the author tackles the relation between temporality and surprise. The main aim of this article is to prove how dialogue, thanks to its playful character (Gadamer), renders possible the moment of surprise, and thereby, enables a deeper understanding to occur between I and Thou (Buber).